Effect of Physical Therapy Treatment in Knee Osteoarthritis with and without Wedge Insole: Randomized Controlled Trial: Physical Therapy Treatment in Knee Osteoarthritis With Wedge Insole - Mohammad Shah, Syed; Ashraf, Naveeda; Hassan, Danish; Waseem Akhtar, Muhammad (Pakistan BioMedical Journal, 2022)
The purpose of this study was to determine the effects of physical therapy treatment in knee osteoarthritis with and without wedge support.Methods: This randomized controlled trail was conducted at Outpatient Department of Physical Therapy, Mayo Hospital, Lahore and Mid City Hospital, Lahore. Eighty patients with knee osteoarthritis were selected using a predefined inclusion and exclusion criteria and randomly allocated in two treatment groups; Group A (Routine physiotherapy treatment) and Group B (Routine physiotherapy with wedge insole). Outcome were recorded at the start and at the end of treatment at 3 weeks in terms of pain and disability as recorded on Numeric Pain Rating Scale (NPRS) and Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) respectively. The collected data was entered and analyzed using SPSS v25 with p value < 0.05 as significant.Results: At the end of the third week, there was a statistically significant difference between the two treatment groups in terms of VAS (Mean Difference 1.55; p value 0.05) and WOMAC (Mean Difference 5.53; p value 0.0001). A statistically significant difference in before and after treatment VAS and WOMAC score was also noted within each group with p value <0.0001.Conclusion: In comparison to conventional physical therapy alone, adding wedge insoles to the routine physical therapy treatment of Knee Osteoarthritis results in better pain relief and function improvement.